2009
DOI: 10.1002/joc.1903
|View full text |Cite
|
Sign up to set email alerts
|

Effect of late 1970's climate shift on tropospheric biennial oscillation—role of local Indian Ocean processes on Asian summer monsoon

Abstract: ABSTRACT:The tropical climate has undergone noticeable changes on interdecadal time scales. The climate shift that occurred in the late 1970s attained enormous attention owing to its global-scale variations in ocean temperature, heat content and El Nino Southern Oscillation (ENSO) properties. Earlier studies presented the effect of this shift on ENSO and the Asian summer monsoon-ENSO relationship. The present study is an attempt to investigate the effect of late 1970's climate shift on tropospheric biennial os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The variation may not be attributed to rainfall measurement error since, in many areas of the world, a significant change in general atmospheric circulation was observed during that decade (e.g. Ivanov and Evtimov 2009;Pillai and Mohankumar 2010;Trenberth and Hurrell 1994;Wang et al 2010). For instance, according to Wang et al (2010), "in the mid-1970s, the atmospheric circulation underwent significant changes in many regions of the world".…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The variation may not be attributed to rainfall measurement error since, in many areas of the world, a significant change in general atmospheric circulation was observed during that decade (e.g. Ivanov and Evtimov 2009;Pillai and Mohankumar 2010;Trenberth and Hurrell 1994;Wang et al 2010). For instance, according to Wang et al (2010), "in the mid-1970s, the atmospheric circulation underwent significant changes in many regions of the world".…”
Section: Discussionmentioning
confidence: 94%
“…This change in general atmospheric circulation affected the variability of climate indices and of hydroclimatic variables (temperature, precipitation, wind, streamflow, etc.). As for the tropical region, Pillai and Mohankumar (2010) noted that "the tropical climate system has undergone many secular changes on interdecadal timescales as the climate shift occurred in 1976. Along with the shift, a significant increase in sea surface temperature was found in the tropical central and eastern Pacific and Indian Ocean".…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, analysing the CDHE events using the CDHE indices will help quantify CDHE severities in India as well which is lacking in the literature. Past studies have reported on the role of large‐scale circulation patterns like ENSO, PDO, Equatorial Indian Ocean Monsoon Oscillation (EQUINOO), and Indian Ocean Dipole (IOD) in modulating temperature and precipitation‐based events in India (Murari et al, 2016; Pattanayak et al, 2017; Pillai & Mohankumar, 2010). However, no studies in the past have reported how large‐scale climate patterns such as ENSO, PDO, EQUINOO and IOD influence CDHEs in India.…”
Section: Introductionmentioning
confidence: 99%
“…Prominent decadal variation has been observed in the biennial rainfall relationship over the tropical eastern hemisphere (e.g. Ashok et al 2014;Meehl and Arblaster 2011;Pillai and Mohankumar 2010;Wu 2016). However, it remains necessary to determine if there are significant decal changes in the biennial rainfall relationship between CA and ESA over the tropical western hemisphere.…”
Section: Introductionmentioning
confidence: 99%